An Innovative Approach to Environmental Literacy: The Sustainable RADEC Learning Model for Elementary Schools - Lestari, Hana; Rahmawati, Ima; Ali, Mohammad; Sopandi, Wahyu; Wulan, Ana Ratna (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis study aims to design and develop an Education of Sustainable Development-oriented RADEC learning design model for enhancing the environmental literacy of elementary school students. The research approach employed consists of four key stages: (1) problem identification, (2) defining various objectives, (3) design and development, and (4) product validation. The research sample was selected using purposive sampling and comprised six elementary school teachers from various grade levels, ranging from grade 1 to grade 6. Data collection involved the use of scaled questionnaires and interviews. The collected data were then analyzed using the Explanatory Sequential Mixed Method. The results indicate that the curriculum design for the ESD-oriented RADEC learning model is suitable for implementation in elementary schools. This conclusion is supported by the mean score of 3.98 and a standard deviation of 0.22, showing a consistent range of responses among experts. In other words, the experts unanimously agree that the product design is appropriate for classroom learning. To further assess the validity of the design, a one-way ANOVA test was conducted to determine if there were significant differences in the opinions of experts across various domains (ESD, RADEC, Environmental Literacy, and Basic Education). The results revealed that the F score and p-value exceeded Î± = 0.05, indicating no significant differences in the perceptions of the experts involved in the study. In summary, the experts reached a consensus that the product design exhibits a high level of feasibility, earning a